2023
DOI: 10.3390/ijms24032258
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antioxidant, and Neuroprotective Effects of Polyphenols—Polyphenols as an Element of Diet Therapy in Depressive Disorders

Abstract: Depressive disorders can affect up to 350 million people worldwide, and in developed countries, the percentage of patients with depressive disorders may be as high as 10%. During depression, activation of pro-inflammatory pathways, mitochondrial dysfunction, increased markers of oxidative stress, and a reduction in the antioxidant effectiveness of the body are observed. It is estimated that approximately 30% of depressed patients do not respond to traditional pharmacological treatments. However, more and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 289 publications
0
18
0
Order By: Relevance
“…Polyphenols are very well-known antioxidants and thousands of scientific works have verified this activity for these ubiquitous natural compounds. A countless number of them, including many of those encountered in BP, have been conducted either at experimental or clinical levels, and have concerned many types of human diseases [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. The development of these studies being beyond the scope of our current paper, we will not develop these results here.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols are very well-known antioxidants and thousands of scientific works have verified this activity for these ubiquitous natural compounds. A countless number of them, including many of those encountered in BP, have been conducted either at experimental or clinical levels, and have concerned many types of human diseases [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. The development of these studies being beyond the scope of our current paper, we will not develop these results here.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies showed that resveratrol might reduce depressive behaviors in animal models (Nabavi et al, 2017; Shayganfard, 2020; Winiarska‐Mieczan et al, 2023; Y. Y. Xu et al, 2017). Given the complex and not fully understood pathogenesis of depression, researchers have considered multiple mechanisms for the antidepressant‐like effects of resveratrol.…”
Section: Stilbenes In Neuropsychiatric and Neurological Disordersmentioning
confidence: 99%
“…Levels of vitamins A, C, and E as well as other small antioxidants (such as uric acid, albumin, and coenzyme Q10) are lower in depressed patients and negatively correlate with the disease’s severity [ 86 , 101 , 102 , 103 ]. Hence, various dietary approaches, such as supplementation with the bioactive antioxidative ingredients from certain types of food, have been considered as adjuvant strategies for mitigating depressive symptoms [ 104 , 105 , 106 ]. Several studies have shown that supplementation with vitamin C may induce antidepressant effects and improve moods [ 107 , 108 ].…”
Section: Neuropathological Mechanisms Underlying the Development Of D...mentioning
confidence: 99%